2019
DOI: 10.3390/ph12030117
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Anti-Cancer Activities of Ginsenoside Rg3 on Triple Negative Breast Cancer Cell Models

Abstract: Ginsenoside Rg3 (Rg3) has two epimers, 20(S)-ginsenoside Rg3 (SRg3) and 20(R)-ginsenoside Rg3 (RRg3), and while Rg3 itself has been reported to have anti-cancer properties, few studies have been reported on the anti-cancer effects of the different epimers. The aim was to investigate the stereoselective effects of the Rg3 epimers on triple negative breast cancer (TNBC) cell lines, tested using cell-based assays for proliferation, apoptosis, cell cycle arrest, migration and invasion. Molecular docking showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 60 publications
0
53
0
Order By: Relevance
“…We have shown that blockers of the AQP1 water channel such as AqB013 [ 96 ], AqB050 [ 97 ] and bacopaside II [ 98 ] inhibit tube formation in endothelial cells. We have also shown that SRg3 stereoselectively inhibited AQP1-mediated transport of water [ 12 ]. Decreased expression of AQP1 with Rg3 treatment was also shown in a prostate cancer cell line [ 99 ].…”
Section: Molecular Mechanisms Of Rg3 In Targeting Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that blockers of the AQP1 water channel such as AqB013 [ 96 ], AqB050 [ 97 ] and bacopaside II [ 98 ] inhibit tube formation in endothelial cells. We have also shown that SRg3 stereoselectively inhibited AQP1-mediated transport of water [ 12 ]. Decreased expression of AQP1 with Rg3 treatment was also shown in a prostate cancer cell line [ 99 ].…”
Section: Molecular Mechanisms Of Rg3 In Targeting Angiogenesismentioning
confidence: 99%
“…Rg3 is one of the most studied and pharmacologically active ginsenosides, with stereoselective activities by the epimers SRg3 and RRg3 [ 11 , 12 ]. The chemistry of Rg3 epimers could explain this stereoselective activity.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of AQP1 in the leading edges of migrating cells has been linked to enhanced motility, as documented in neural crest (McLennan et al, 2020) and various types of cancer cells including colon cancer, gliomas, breast cancer, and endothelial cells involved in angiogenic responses (McCoy and Sontheimer, 2007;Pei et al, 2016a;Nakhjavani et al, 2019;Tomita et al, 2019). AQP1 is a dual water and ion channel (Anthony et al, 2000;Yu et al, 2006;Campbell et al, 2012;Kourghi et al, 2018), which has been suggested to accelerate cell migration by enabling parallel water and cation entry (Yool et al, 2009;Pei et al, 2019), promoting the cellular lamellipodial and filopodial extensions needed for forward movement.…”
Section: Transcriptomic Analysis Of Additional Channels and Transportmentioning
confidence: 99%
“…Helen et al [32] also reported that the triterpenoid saponins bacopaside I and bacopaside II can synergistically reduce the transcriptional expression of AQP1, and inhibit proliferation, migration and invasion in MDA-MB-231 cells. Similarly, ginsenoside Rg3, a compound with anticancer activity isolated from ginseng, inhibits AQP1 to attenuate cell proliferation through a mechanism that involves downregulation of AQP1 to induce cell cycle arrest in G0/G1 phase by inhibiting cyclin D and E and inhibition of chemoattractant-induced cell migration and invasion by blocking AQP1-mediated water flux in MDA-MB-231 cells [33]. These findings indicate that AQP1 plays an important role in the development and progression of TNBC.…”
Section: Aqp Channelsmentioning
confidence: 88%